Drug-coated balloon in the treatment of coronary artery de-novo large lesions angiography: Drug-coated balloon in coronary artery - Cai, Xingyou; Hong, Xin; Wang, Yuli; Li, Yafei; Xu, Guidong (Cellular and Molecular Biology, 2024)
The superiority of drug-coated balloon (DCB) in treating small vessels, branching lesions, and high-risk bleeding lesions in coronary heart disease patients has been confirmed. However, its safety and efficacy in large vessels are still unclear. We aimed to investigate whether the efficacy of DCB in large vessels is not inferior to that of drug-eluting stent (DES). From November 2019 to April 2022, a total of 88 patients in our hospital who underwent coronary angiography for the first time and decided to receive DCB or DES treatment were selected. Indicators including late lumen loss (LLL), major adverse cardiovascular event (MACE) rate, major bleeding and all-cause mortality were evaluated at 9 months and 1-year post percutaneous coronary intervention (PCI) therapy. The primary endpoint of 9-month LLL was -0.07 in the DCB group and 0.19 mm in the DES group (p value＜0.001). 1-year cumulative MACE rates were similar in the DCB and DES groups (3.03% vs. 7.23%, P=0.519), TLR rates were similar (3.03% vs. 7.23%, P=0.519), Major bleeding was similar (3.03% vs. 5.45%, P=0.580), and 1 case of Cardiac death in DES group. For LLL, the DCB-only strategy was non-inferior to DES in treating de novo large lesions in the coronary arteries. Furthermore, the efficacy of DCB was comparable to DES at 1 year of follow-up for secondary clinical endpoints.